A Transdiagnostic Perspective on Social Anhedonia - Barkus, Emma; Badcock, Johanna C. (Frontiers in Psychiatry, 2019)
Humans are highly social beings, yet people with social anhedonia experience reduced interest in or reward from social situations. Social anhedonia is a key facet of schizotypal personality, an important symptom of schizophrenia, and increasingly recognized as an important feature in a range of other psychological disorders. However, to date, there has been little examination of the similarities and difference in social anhedonia across diagnostic borders. Here, our goal was to conduct a selective review of social anhedonia in different psychological and life course contexts, including: the psychosis continuum, depressive disorder, posttraumatic stress disorder, eating disorders and autism spectrum disorders, along with developmental and neurobiological factors. Current evidence suggests that the nature and expression of social anhedonia varies across psychological disorders with some groups showing deficient learning about, enjoyment from, and anticipation of the pleasurable aspects of social interactions whilst for others some of these components appear to remain intact. However, study designs and methodologies are diverse, the role of developmental and neurobiological factors are not routinely considered, and direct comparisons between diagnostic groups are rare - which prevents a more nuanced understanding of the underlying mechanisms involved. Future studies, parsing the wanting, liking and learning components of social reward will help to fill the gaps in the current knowledge base. Consistent across disorders is diminished pleasure from social situations, subsequent withdrawal and poorer social functioning in those who express social anhedonia. Nonetheless, feelings of loneliness often remain, which suggests that the need for social connection is not entirely absent. Adolescence is a particularly important period of social and neural development and may provide a valuable window on the developmental origins of social anhedonia. Adaptive social functioning is key to recovery from mental health disorders therefore understanding the intricacies of social anhedonia will help to inform treatment and prevention strategies for a range of mental disorders.